1968
DOI: 10.1021/jf60158a027
|View full text |Cite
|
Sign up to set email alerts
|

Heptachlor and heptachlor epoxide residues on fall-treated alfalfa and in milk and cow tissues

Abstract: Heptachlor and heptachlor epoxide residues in trace amounts occurred in alfalfa harvested from fields treated the previous fall at 0.25, 0.50, and 1.00 pound of heptachlor per acre.Heptachlor epoxide residues subsequently appeared in the fat tissue and milk of cows that ingested the treated hay over a period of 30 days. The highest concentration of residue in milk occurred between the 18th and 24th days of the feeding period and averaged 13, 26, and 49 p.p.b. for the test animals in each group. Re-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1971
1971
1991
1991

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The data in Table 2 is not included in the graphic representations of Figures 1-6. Previous studies (Waldron et at, 1968;Cummings et al, 1967) have shown that the elimination of pesticide residues from animal and poultry bodies generally follows a half-life function with a rapid disappearance of organochlorine residues from tissues in the first few days or weeks following withdrawal of contaminated feed and a gradual leveling of the curve over an extended period of time. Because no data was obtained until 8 weeks following the return to the basal diet, a disappearance curve depiction is impractical.…”
Section: Resultsmentioning
confidence: 98%
“…The data in Table 2 is not included in the graphic representations of Figures 1-6. Previous studies (Waldron et at, 1968;Cummings et al, 1967) have shown that the elimination of pesticide residues from animal and poultry bodies generally follows a half-life function with a rapid disappearance of organochlorine residues from tissues in the first few days or weeks following withdrawal of contaminated feed and a gradual leveling of the curve over an extended period of time. Because no data was obtained until 8 weeks following the return to the basal diet, a disappearance curve depiction is impractical.…”
Section: Resultsmentioning
confidence: 98%
“…Pesticide residues found on the leaves of corn plants grown within the treated area are presented in Table I. The total pesticide concentration reached a maximum of over 1.8 ppm on the lower leaves by the October harvest time, a level that is unacceptable in dairy cattle fodder (Waldron et al, 1968). The increasing pesticide burden was due primarily to steadily increasing dieldrin concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…With crops used for dairy cattle feed, even extremely small accumulations of certain pesticides on the plants will result in measurable residues in the milk. For example, cows feeding for 30 days on alfalfa hay containing less than 0.04 ppm heptachlor residues produced milk containing 0.013 ppm heptachlor epoxide (Waldron et al, 1968). Dieldrin levels in a forage crop as low as 0.02 ppm led to unacceptable contamination of milk (Harris and Sans, 1969).…”
mentioning
confidence: 99%
“…Extraction procedures for the feed ingredient samples followed in general the principles published in the literature for extraction of organochlorine insecticides (Mills etal., 1963;Minyard and Jackson, 1963;Cummings et al, 1967;Waldron et al, 1968;and Waldron and Goleman, 1969) but with modifications adaptable to the techniques of this laboratory. Additional modifications in procedures, solvent systems, elution techniques, gas chromatographic operation, etc.…”
Section: Methodsmentioning
confidence: 99%